Production and Physiological Quality of Seeds of Mini Watermelon Grown in Substrates with a Saline Nutrient Solution Prepared with Reject Brine - Tatianne Raianne Costa Alves; Salvador Barros Torres; Emanoela Pereira de Paiva; Roseane Rodrigues de Oliveira; Renata Ramayane Torquato Oliveira; Afonso Luiz Almeida Freires; Kleane Targino Oliveira Pereira; Douglas Leite de Brito; Charline Zaratin Alves; Alek Sandro Dutra; Clarisse Pereira Benedito; Alberto Soares de Melo; et al. (Plants, 2022)
The economically profitable production of crops is related, among other factors, to seed quality, the production system, and the water used in irrigation or preparation of nutrient solutions. Therefore, the objective was to evaluate the phenology, production, and vigor of seeds of mini watermelons grown in saline nutrient solution and different substrates. In the fruit and seed production phase, the experiment occurred in a greenhouse with five electrical conductivities of water for nutrient solution preparation, ECw (0.5, 2.4, 4.0, 5.5, and 6.9 dS m−1), and two growing substrates (coconut fiber and sand). We evaluated the physiological quality of seeds previously produced under the five electrical conductivities of water and two substrates. High salinities for the hydroponic cultivation of the mini watermelon cultivar ‘Sugar Baby’ accelerated fruit maturation and crop cycle, decreasing fruit size. However, in both substrates, the seed production of mini watermelons, seed viability, and seed vigor occurred adequately with a reject brine of 6.9 dS m−1 in the hydroponic nutrient solution. The seed production of ‘Sugar Baby’ mini watermelons using reject brine in a hydroponic system with coconut fiber and sand substrates is viable in regions with water limitations.